Sustainable monitoring of roe deer in public hunting areas in the Spanish Pyrenees - Herrero, J.; Torres, R. T.; Prada, C.; García-Serrano, A.; Giménez‐Anaya, A.; Fernández, O. (Forest Systems, 2013)
Aim of study: Monitoring trends in animal populations is essential for the development of appropriate wildlife management strategies. Area of study: The area is situated in the southern Pyrenees (Aragon), Spain. Material and methods: To measure the abundance, population trends, sex ratio, and mortality of roe deer populations, we analyzed data from i) driven hunts for wild boar (hunting seasons 1995/96 – 2009/10, n = 1,417, ii) itineraries, which were used to calculate the KAI and density using DS (2003 – 2010, n = 310 itineraries), iii) roe deer carcass recoveries (2006 – 2010, n = 100), and iv) data from the deer hunting quota fulfillment (2006 – 2010, n = 325 hunted animals. Main results: Based on DS, in 2010, the average density of roe deer populations was 2.3 km-2 (CV 17%). Based on the KAI and the battues, the estimated average annual rate of increase was 5.8% and 4.3%, respectively. Based on the KAI and the carcass recoveries, the estimates of the population sex ratio were 0.75 (n = 641) and 0.9 (n = 100) males per female, respectively. Carcass recoveries indicated that mortality was highest in late winter and early spring. The average body masses and sizes of males and females were within the ranges reported for other Iberian and European populations. Research highlights: Monitoring should be continued in the Aragon population of roe deer, although larger sample sizes are required to increase the accuracy of estimates and assessments of the impact of management actions. Key words: Capreolus capreolus; hunting bag; distance sampling; KAI; Spain; rangers; long-term monitoring.